Ultrathin lithium ion battery implantable temperature sensor and preparation method thereof
By combined with laser activation Selective metalization and ink direct writing 3D printing technology, the ultra -thin and thin lithium -ion battery implantation temperature sensor is prepared, which solves the problem that the existing technologies are difficult to accurately reflect the internal temperature of the battery in the existing technology. Precision monitoring of internal temperature and improvement of battery performance.
Patent Information
- Application Number
- CN202411272403.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2044-09-11
AI Technical Summary
Existing external sensors of existing lithium-ion batteries are difficult to accurately reflect the temperature changes inside the battery, and the process is complex and costly, which affects the sealing and electrochemical properties of the battery.
Laser activation selective metallization (LISM) technology is combined with ink direct writing 3D printing technology to prepare an ultra-thin implantable temperature sensor, which can monitor single-point and multi-point temperature inside the lithium-ion soft-pack battery.
It achieves accurate monitoring of the internal temperature of lithium-ion batteries, reduces the size and cost of the battery, improves the sealing and electrochemical performance of the battery, and supports thermal management and safety warning of the battery.
Smart Images

Figure CN119334495A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of temperature sensors, and relates to an ultra-thin lithium-ion battery implantable temperature sensor and a preparation method thereof, and specifically relates to a lithium-ion battery safety monitoring implantable temperature sensor and its application in lithium-ion battery thermal management and safety warning. Background Art
[0002] Lithium-ion batteries have been widely used in daily electronic products, electric vehicles, mobile communications and other fields due to their high energy density, long cycle life and lightweight. However, safety accidents such as spontaneous combustion and explosion of lithium-ion batteries have occurred frequently in recent years, and its safety issues have become the focus of attention. Battery safety can be affected by many factors, such as internal factors such as battery material defects and aging, as well as external factors such as overcharging, over-discharging, impact and puncture. At the same time, the heat inside the battery is difficult to diffuse quickly, resulting in a continuous rise in temperature, and eventually the battery will experience thermal runaway, resulting in serious consequences such as spontaneous combustion and explosion.
[0003] The key to monitoring the safety status of lithium-ion batteries is advanced sensors and sensing technology. The most direct and common way to use sensors for lithium-ion battery monitoring is to place them on the surface of lithium-ion batteries to directly sense the temperature, pressure and other information on the surface of lithium-ion batteries.
[0004] At present, considerable achievements have been made in the external safety monitoring of lithium-ion batteries. Hu et al. (X. Peng, J. Han, Q. Zhang, Y. Xiang, X. Hu. Real-time mechanical and thermal monitoring of lithium batteries with PVDF-TrFE thin films integrated within the battery. Sensors and Actuators A: Physical, 2022, 388, 113484.) prepared a new array sensor and used it to monitor the surface temperature and pressure of lithium-ion batteries. The sensor array consists of piezoelectric / thermoelectric polyvinylidene fluoride-trifluoroethylene (PVDF-TrFE) and a thin-film transistor array. The manufactured sensor array monitors dynamic pressure and temperature simultaneously, and can locate mechanical damage to lithium-ion soft-pack batteries during service.
[0005] Hayden et al. (Hayden L. Atchison, Zachary R. Bailey, David A. Wetz, Matthew Davis, John M. Heinzel. Fiber Optic Based Thermal and Strain Sensing of Lithium-Ion Batteries at the Individual Cell Level. Journal of The Electrochemical Society, 2021, 168, 040535.) used an optical distributed sensor detector (Optical Distributed Sensor Interrogator, ODiSI) to measure the surface temperature and shell deformation of 18650 batteries under normal and abnormal conditions. After many experiments, it has been proved that ODiSI can measure temperature and stress / strain changes respectively, and has very high repeatability, which is a very promising lithium-ion battery monitoring technology.
[0006] Bliss et al. (Y.Hua, A.Cordoba-Arenas, N.Warner, G.Rizzoni, A multi time-scale state-ofcharge and state-of-health estimation framework using nonlinearpredictive filter for lithium-ion battery pack with passive balancecontrol. J.Power Sources, 2015, 280, 293.) proposed a small, low-power, multi-frequency (1-1000Hz) impedance-based battery management system for multi-cell batteries of different capacities. Compared with the traditional lithium-ion battery management system (Battery Management System, BMS), this technology tracks and responds to emerging mismatches and other electrical and thermal anomalies in each individual battery and takes action.
[0007] Based on the above existing technologies, using sensors outside lithium-ion batteries to safely manage and track the status of batteries is a relatively simple and mature method, and many electric vehicles have sensors placed outside the battery in the battery module. However, this will inevitably increase the battery volume and change the battery shape. More importantly, the parameters monitored outside the battery cannot truly reflect the real-time changes in parameters such as temperature and pressure caused by various chemical reactions inside the battery. Especially when the temperature or pressure changes suddenly, the external monitoring cannot detect these changes quickly. When the external temperature also changes significantly, the battery is likely to have thermal runaway or is on the verge of thermal runaway; at the same time, these measurements and related protocols have not successfully ensured battery safety or improved efficiency. The data of maliciously aged and over-discharged batteries convincingly show that such BMS cannot identify battery mismatches and emerging faults. In view of this, in order to better monitor and manage the status of battery safety and performance in real time, the external-to-implantable sensor is an inevitable trend in the development of high-performance and ultra-safe lithium-ion batteries in the future.
[0008] Monitoring the surface temperature of the battery pack cannot accurately reflect the temperature inside the battery, and external parameter monitoring cannot fully and accurately simulate and reflect the electrochemical changes inside the battery, so it is impossible to effectively evaluate the potential thermal runaway risk of the battery cell. To address this problem, scholars have successively developed a variety of implantable thermocouples, thermal resistance, and fiber optic sensors to monitor the internal temperature of the battery, providing a variety of feasible solutions for preventing battery safety.
[0009] Li et al. (Z.Li, JZ, B.Wu, J.Huang, ZN, Y.Sun, F.An, N.Wu. Examining temporaland spatial variations of internal temperature in large-format laminatedbattery with embedded thermocouples. Journal of Power Sources, 2013, 241, 536.) used thermocouples in a 25Ah soft-pack lithium-ion battery to detect the temperature inside the battery in real time. The results showed that the temperature difference between the inside and outside of the battery was 1.1°C, and the internal thermal response time was tens of seconds longer than that of the outside. In addition, during the 1.5C discharge process, the temperature change on the surface of the battery cell was greater than 10°C, which was much higher than the temperature change on the surface of the battery pack. Therefore, 12 thermocouples need to be arranged to reflect the actual temperature of the surface of the battery cell.
[0010] Wang et al. (C.-Y.Wang, G.Zhang, S.Ge, T.Xu, Y.Ji, X.-G.Yang.Lithium-ionbattery structure that self-heats at low temperatures.Nature, 2016, 529, 515.) implanted a platinum Pt thermal resistor (PT1000) into a lithium button battery to monitor its internal temperature in real time. The results showed that the temperature change trend was the same as that measured by the microcalorimeter. Secondly, the embedded sensor has a large impact on the electrochemical performance, up to 50% at a 2C rate.
[0011] Micael et al. (Wenxin Mei, Zhi Liu, Chengdong Wang, Chuang Wu, Yubin Liu, Pengjie Liu, Xudong Xia, Xiaobin Xue, Xile Han, Jinhua Sun, Gaozhi Xiao, Hwa-YawTam, Jacques Albert, Qingsong Wang, Tuan Guo. Operando monitoring of thermal runaway in commercial lithium-ion cells via advanced lab-on-fibertechnologies. Nat Commun, 2023, 14, 5251.) proposed a hybrid sensor consisting of a Bragg grating and a Fabry-Perot cavity that can be used to simultaneously monitor strain and temperature. The dual-function sensor is embedded in a lithium-ion pouch cell to monitor and distinguish in-situ internal strain and temperature changes in three different regions (top, middle, and bottom) of the battery.
[0012] Mei et al. (Li W, Li L, Sun Q. Direct Fabrication of High-resolution and high-performance flexible electronics via surface-activation-localized electroless plating. Chemical Engineering Journal, 2021, 416, 127644.) developed a compact and multifunctional fiber optic sensor (12 mm in length and 125 μm in diameter) that can be inserted into commercial 18650 batteries to continuously monitor the internal temperature and pressure effects during battery thermal runaway.
[0013] However, in order to avoid the influence of the electrolyte in the battery on the performance of the temperature sensor, the embedded sensors must be packaged before they can be arranged on the surface of the battery cell, and then connected to the electrodes to monitor the temperature inside the battery. This assembly process is relatively complex and costly, and the arrangement of multiple sensors will make the inside of the battery uneven, resulting in poor sealing of the battery; in addition, the thermocouple is large in size, and after integration with the battery, it has a great impact on the quality and volume of the battery, seriously affecting the electrochemical performance of the battery. Fiber optic sensors are small in size and flexible. After being implanted in lithium-ion batteries, the battery performance loss is small. However, there are still many challenges in the fine analysis of optical signals. Based on the above problems, these built-in sensor solutions are currently stagnant in the laboratory stage and cannot be applied to actual production.
[0014] In summary, internal temperature monitoring can directly monitor the surface temperature of the battery cell, which is an effective way to ensure the safe operation of the battery. However, implantable temperature sensors currently face problems such as complex processes, high costs, poor sealing, and chaotic wiring, and cannot be widely used. Therefore, the development of implantable flexible ultra-thin temperature sensors / sensor arrays to accurately monitor the internal temperature of lithium-ion batteries in real time is crucial for battery thermal management and safety warning. Summary of the invention
[0015] In order to solve the above-mentioned problems in the prior art, the present invention provides an ultra-thin lithium-ion battery implantable temperature sensor and a preparation method thereof. The present invention realizes the ultra-thin requirement of the sensor by combining laser activated selective metallization (LISM) technology with ink direct writing 3D printing technology, and implants it into a lithium-ion soft-pack battery for single-point and multi-point temperature monitoring, which is of great significance to the thermal management and thermal design of lithium-ion batteries.
[0016] To achieve the above objectives, the present invention is implemented by adopting a technical solution consisting of the following technical measures.
[0017] In one aspect, the present invention provides a method for preparing an ultra-thin lithium-ion battery implantable temperature sensor, which mainly comprises the following steps:
[0018] (I) Preparation of flexible substrate metal electrodes based on LISM technology
[0019] (1-1) mixing a laser sensitizer with a solvent to obtain a laser sensitizer suspension or solution, then coating the suspension or solution on the surface of a flexible polymer film, and then removing the solvent to obtain a flexible polymer film having a sensitizer coating;
[0020] The flexible polymer film material is a polyimide film (PI) or a polyethylene terephthalate film (PET);
[0021] The laser sensitizer is an organic copper sensitizer or an inorganic copper sensitizer;
[0022] (1-2) irradiating the surface of the flexible polymer film having the sensitizer coating obtained in step (1-1) with a laser, forming an activation pattern of an electrode in the irradiated area, and then washing away excess laser sensitizer to obtain a laser-activated flexible polymer film;
[0023] (1-3) immersing the laser-activated flexible polymer film obtained in step (1-2) into a metal plating solution for chemical plating to form a flexible metal electrode pattern at the activated pattern, thereby preparing a flexible substrate metal electrode based on LISM technology;
[0024] (II) Preparation of implantable temperature sensor
[0025] (2-1) The following raw materials are mixed in parts by weight to prepare a carbon-based temperature-sensitive functional ink:
[0026] Nanocellulose (CNF) 3-5 parts,
[0027] Single-walled carbon nanotubes (SWCNT) 1-1.5 parts,
[0028] 93.5 to 96 parts of solvent,
[0029] Among them, nanocellulose, single-walled carbon nanotubes and solvents totaled 100 parts;
[0030] (2-2) loading the carbon-based temperature-sensitive functional ink obtained in step (2-1) into the printing syringe of an ink direct writing 3D printer, and printing 2 to 4 layers of a grid-like thermosensitive unit precursor on the flexible substrate metal electrode obtained in step (1-3);
[0031] The printed product is then freeze-cured and dried to obtain an implantable temperature sensor.
[0032] Herein, the laser sensitizer in step (1-1) is an organic copper sensitizer or an inorganic copper sensitizer, both of which are conventional laser sensitizers in the art. Those skilled in the art can select a suitable organic copper sensitizer or inorganic copper sensitizer according to specific needs and process requirements.
[0033] In order to better illustrate the present invention and provide a preferred technical solution for reference, the laser sensitizer in step (1-1) is selected from any one of Cu2(OH)PO4, CuBr, Cu2O, copper (II)-phenanthroline complexes, and copper (II)-phthalocyaninetetrasulfonate.
[0034] In this article, the solvents described in steps (1-1) and (2-1) are conventional solvents in the field of chemical materials. Those skilled in the art can select suitable solvents according to specific needs and process requirements, and can also optimize them according to their applicable purposes. For example, in step (1-1), the solvent plays a role in uniformly dispersing the laser sensitizer so that it is suitable for scraping on the surface of the flexible polymer film material, and in step (2-1), the solvent is the main ink component in the ink direct writing 3D printing technology. Those skilled in the art can optimize them according to the conventional ink solvents for the ink direct writing 3D printing technology in the prior art.
[0035] In order to better illustrate the present invention and provide a preferred technical solution for reference, the solvent selected in steps (1-1) and (2-1) includes any one of ethanol, deionized water, ethylene glycol, ammonia, dimethylformamide, and dimethyl sulfoxide. Theoretically, the solvents in steps (1-1) and (2-1) can be the same solvent or different solvents; in one preferred technical solution, the solvent in step (1-1) is ethanol; the solvent in step (2-1) is deionized water.
[0036] In this article, the laser sensitizer and the solvent are mixed in step (1-1) to obtain a laser sensitizer suspension or solution. The ratio of the laser sensitizer to the solvent can be directly referred to the conventional application method of the laser sensitizer in the prior art, such as the ratio recommended in the product manual. In order to better illustrate the present invention and provide a technical solution for reference, the laser sensitizer and the solvent in step (1-1) are mixed in a ratio of 1g: (15-40)ml.
[0037] In one of the technical solutions, in order to enable the irradiated area in step (1-2) to form a better activation pattern, the suspension or solution described in step (1-1) is scraped onto the surface of the flexible polymer film, preferably to form a coating of 40 to 60 μm thick, and then the solvent is removed to obtain a flexible polymer film with a sensitizer coating.
[0038] Herein, the removal of solvent in step (1-1) is performed by a conventional method for removing solvent from coatings after coating in the chemical industry. For example, when the solvent is ethanol, the ethanol is allowed to evaporate by standing at room temperature.
[0039] One of the inventive points of the present invention is that, based on the prior laser activated selective metallization (LISM) technology of the applicant of the present invention, it is found that the specific process parameters of laser irradiation will significantly affect the quality and peeling strength of the activated pattern and the flexible metal electrode pattern. The inventors of the present invention have found through a large number of orthogonal experiments that under specific laser parameters and laser irradiation times, a metal coating with uniform thickness and high peeling strength can be formed, while showing excellent continuity and fineness.
[0040] Based on the above invention, in one of the technical solutions, the step (1-2) uses a laser to irradiate the surface of the flexible polymer film material with a sensitizer coating obtained in the step (1-1), and forms an activation pattern of an electrode in the irradiated area. Specifically, the surface of the flexible polymer film material with a sensitizer coating is irradiated with a laser twice. The laser frequency of the first laser irradiation is 50kHz, the laser power is 6W, and the laser scanning speed is 2000mm / s. The laser frequency of the second laser irradiation is 50~70kHz, the laser power is 6~7W, and the laser scanning speed is 2000mm / s.
[0041] In this article, the activation pattern of the electrode is formed in the irradiated area in step (1-2), wherein the activation pattern of the electrode is selected from a conventional electrode line pattern, such as an activation pattern of an interdigitated electrode. Further, multiple electrode line array patterns, such as an activation pattern of an interdigitated electrode array, can also be formed based on the prior art.
[0042] It should be noted that the size and dimensions of the activated pattern of the formed electrode can be designed according to the relevant public specifications of microelectrodes in the prior art, and its size and dimensions are preferably matched with the grid-shaped thermosensitive unit precursor described below.
[0043] Herein, the excess laser sensitizer is washed away in step (1-2), usually by using the solvent in step (1-1), or other conventional methods in the art.
[0044] In this article, the metal plating solution described in step (1-3) is a metal plating solution conventionally used in the field of chemically plating metal electrodes in this technical field. Those skilled in the art can directly select an appropriate public metal plating solution formula to configure the corresponding metal plating solution according to existing processes or actual needs. In one technical solution, the metal plating solution selected in step (1-3) includes a copper metal plating solution, a nickel metal plating solution, a silver metal plating solution, a chromium metal plating solution or a gold metal plating solution.
[0045] In one technical solution, the metal plating solution in step (1-3) is a copper metal plating solution, and chemical copper plating is performed according to the following reaction formula:
[0046] Cu 2+ +2HCHO+4OH - →Cu+2HCOO - +H2O+H2↑.
[0047] In order to better illustrate the present invention and provide a technical solution for reference, the composition of the metal plating solution in step (1-3) is: 8g / L CuSO4, 30g / L NaKC4H4O6, 3g / L EDTA, 3g / L C6H5Na3O7, 12ml / L HCHO and 150ml / L CH3OH, and the solvent is deionized water.
[0048] Herein, the chemical plating described in step (1-3) is a conventional chemical plating method in the field of chemical plating of metal electrodes. Those skilled in the art can determine the specific chemical plating process conditions according to the chemical reaction conditions of the selected metal plating solution.
[0049] In order to better illustrate the present invention and provide a technical solution for reference, when the metal plating solution is the copper metal plating solution, the chemical plating in step (1-3) is to immerse the flexible polymer film after laser activation in the metal plating solution, and stir it for 12 to 20 minutes at a temperature of 50 to 60°C to prepare a flexible substrate metal electrode based on LISM technology.
[0050] It should be noted that the preparation of the flexible substrate metal electrode based on LISM technology in step (1-3) usually also includes conventional operations such as cleaning after chemical plating. These conventional operations are common knowledge of those skilled in the art and will not be described again.
[0051] In this article, the preparation of the carbon-based temperature-sensitive functional ink follows the common knowledge in the art, and each raw material component is mixed evenly.
[0052] In order to better illustrate the present invention and provide a technical solution for reference, the preparation method of the carbon-based temperature-sensitive functional ink is specifically to mix and stir the raw material components for 20 to 120 minutes at 20 to 35°C and 8000 to 30000 r / min.
[0053] In one technical solution, in order to better adapt the carbon-based temperature-sensitive functional ink in step (2-1), the parameters of the ink direct writing 3D printer in step (2-2) are set to the air pressure at 15-30 psi and the printing needle moving speed at 5-12 mm s-1 .
[0054] In one of the technical solutions, the printed product is freeze-solidified and dried in step (2-2), wherein the printed product is frozen with liquid nitrogen for 2 to 10 minutes and then freeze-dried for at least 12 hours.
[0055] In this article, the 2 to 4 layers of grid-like thermal-sensitive unit precursor described in step (2-2), wherein the number of layers 2 to 4 is the number of slice layers in ink direct writing 3D printing, for example, each layer is a parallel printing wire strip formed by straight line filling printing, and the printing wire strips of adjacent layers are perpendicular to each other to form a grid structure, and therefore, there are at least 2 layers.
[0056] In one of the technical solutions, in order to make the prepared implantable temperature sensor have ultra-light and thin characteristics in terms of size specifications, the single length of the grid-shaped thermistor unit precursor is 7 to 10 mm, the width is 7 to 10 mm, the thickness is 1.5 to 2 mm, and the weight is about 10 to 20 mg.
[0057] In one of the more preferred technical solutions, in order to improve the temperature sensitivity of the prepared implantable temperature sensor, the 2 to 4 layers of grid-shaped thermosensitive unit precursors in step (2-2) are each composed of parallel printed wire strips formed by linear filling printing, the printing needle diameter is 0.5 to 0.7 mm, and the spacing between the printed wire strips is 0.4 to 0.6 mm.
[0058] It should be noted that when the flexible substrate metal electrode based on LISM technology obtained in step (1-3) is an electrode array, the grid-shaped thermosensitive unit precursor in step (2-2) should also form an array corresponding to the electrode array, that is, an array is formed by multiple grid-shaped thermosensitive unit precursors to finally obtain an implantable temperature sensor array.
[0059] One of the main inventive points of the present invention is that a SWCNT / CNF system ink applied to ink direct writing 3D printing technology is developed, and a thermosensitive unit precursor with a grid structure is printed and manufactured on a flexible substrate metal electrode based on LISM technology, realizing an implantable temperature sensor with high sensitivity and temperature sensitivity in a wide temperature range. LISM technology combined with ink direct writing 3D printing technology realizes the ultra-light and thin requirements of the sensor, and it is implanted in the lithium-ion soft-pack battery for single-point and multi-point temperature monitoring, which is of great significance to the thermal management and thermal design of lithium-ion batteries.
[0060] Specifically, firstly, the thermosensitive unit precursor prepared by the technology of the present invention realizes the regulation of thermistor sensitivity and temperature measurement range, and obtains a sensitivity of -1.7%K -1 , high performance characterization in the temperature sensing range of 30 to 70°C.
[0061] Secondly, the implantable temperature sensor array was implanted into the lithium-ion soft-pack battery for multi-point monitoring. The cycle performance and rate performance loss of the soft-pack battery were small. After 20 cycles of 1C rate charge and discharge, the specific capacity remained above 120mAh / g, and after 50 cycles, the specific capacity remained above 118mAh / g, and the coulomb efficiency remained above 99%. The soft-pack battery with the sensor array implanted was subjected to five charge and discharge cycles of 0.2C, 0.5C, 1C, 2C and 0.5C, with specific capacities of 130.1mAh / g, 127.3mAh / g, 113.7mAh / g, 98.1mAh / g and 128.2mAh / g. Although the specific capacity of the soft-pack battery decayed more at 2C rate, the specific capacity recovered to 128.2mAh / g after returning to 0.5C rate, showing good reversibility.
[0062] Based on the above invention points, the ultra-light and thin lithium-ion battery implantable temperature sensor provided by the present invention can be applied to lithium-ion batteries, and can realize thermal management and safety warning of lithium-ion batteries.
[0063] In order to better illustrate the present invention, on the other hand, the present invention also provides a lithium-ion soft-pack battery using the implantable temperature sensor, wherein the implantable temperature sensor is implanted between the negative electrode and the outermost diaphragm of the lithium-ion soft-pack battery, and the implantable temperature sensor is connected to a signal processing module to monitor the internal temperature of the lithium-ion soft-pack battery.
[0064] In this article, the signal processing module includes a single-chip microcomputer and its supporting control system. The resistance signal transmitted by the electrode point is converted into a digital signal through the analog-to-digital converter on the single-chip microcomputer, and transmitted to the central processing unit on the single-chip microcomputer. The temperature size and change are judged by the resistance size and change.
[0065] When the implantable temperature sensor is an implantable temperature sensor array, or when a plurality of implantable temperature sensors are implanted at different positions inside the lithium-ion soft-pack battery, multi-point temperature monitoring can be performed inside the lithium-ion soft-pack battery.
[0066] The present invention has the following beneficial effects:
[0067] 1. The present invention provides an ultra-thin lithium-ion battery implantable temperature sensor and a preparation method thereof. First, based on the laser activated selective metallization (LISM) technology and laser induced carbonization, a metal electrode pattern with high conductivity and high adhesion is successfully manufactured on a flexible polymer film. Further exploration has found that under the conditions of secondary laser irradiation and specific laser parameters, a metal coating with uniform thickness and high peel strength can be formed, while showing excellent continuity and fineness.
[0068] 2. Secondly, by developing a SWCNT / CNF system ink for ink direct writing 3D printing technology, and printing and manufacturing a thermosensitive unit precursor with a grid structure on a flexible substrate metal electrode based on LISM technology, an implantable temperature sensor with high sensitivity in a wide temperature range was realized. LISM technology combined with ink direct writing 3D printing technology realizes the ultra-light and thin requirements of the sensor, and implants it into the lithium-ion soft-pack battery for single-point and multi-point temperature monitoring, which is of great significance to the thermal management and thermal design of lithium-ion batteries.
[0069] 3. Compared with the existing technology, the implantable temperature sensor array is implanted inside the lithium-ion soft-pack battery for multi-point monitoring. The cycle performance and rate performance loss of the soft-pack battery are extremely small, and it shows good reversibility. BRIEF DESCRIPTION OF THE DRAWINGS
[0070] Figure 1 Schematic diagram of the manufacturing process of the implantable temperature sensor / implantable temperature sensor array prepared in Example 1 and Example 5 of the present invention.
[0071] Figure 2 This is a schematic diagram of the structure of the implantable temperature sensor / implantable temperature sensor array prepared in Example 1 and Example 5 of the present invention implanted with a lithium-ion soft-pack battery.
[0072] Figure 3 The laser parameter matrix of the first laser irradiation and the photo of the PI film after laser activation in the present invention. Among them, (a) is the laser parameter matrix of the first laser irradiation; (b) is the photo of the PI film after laser activation.
[0073] Figure 4 The following are photos of the PI film after the second laser irradiation and the photo after chemical copper plating in the present invention. Among them, (a) is a photo of the PI film after the second laser irradiation; (b) is a photo of the PI film after chemical copper plating.
[0074] Figure 5 The SEM images of the PI film surface after the first laser irradiation and the second laser irradiation in Example 1 of the present invention are shown in FIG. (a) and (b) are SEM images of the PI film surface after the first laser irradiation; (c) and (d) are SEM images of the PI film surface after the second laser irradiation.
[0075] Figure 6 The following are photos of the surface of the PI film after the first laser irradiation and the second laser irradiation in Example 1 of the present invention. (a) is a photo of the shape of the interdigitated electrodes on the surface of the PI film after the first laser irradiation; (b) is a photo of the shape of the interdigitated electrodes on the surface of the PI film after the second laser irradiation.
[0076] Figure 7The photographs and SEM images of the flexible substrate metal interdigital electrode prepared based on the LISM technology in Example 1 of the present invention are shown in Figures 1 and 2. (a) and (b) are the overall and detailed photographs of the flexible substrate metal interdigital electrode, respectively; (c) and (d) are the SEM images of the metal interdigital electrodes on the surface of the flexible substrate metal interdigital electrode.
[0077] Figure 8 The following are photos of the flexible substrate metal interdigital electrode array and the implantable temperature sensor array prepared in Example 5 of the present invention. (a) is a photo of the prepared flexible substrate metal interdigital electrode array; (b) is a photo of the implantable temperature sensor array.
[0078] Fig. 9 Comparative line graphs of viscosity / shear rate, storage modulus G', and loss modulus G" of the carbon-based temperature-sensitive functional inks prepared in Examples 2 and 4 of the present invention and Comparative Examples 1 and 2. Among them, (a) is the relationship between the viscosity and shear rate of the carbon-based temperature-sensitive functional ink; (b) is the storage modulus G'; and (c) is the loss modulus G".
[0079] Fig.10 This is a radar chart comparing the comprehensive performance of the carbon-based temperature-sensitive functional inks prepared in Examples 2 and 4 of the present invention and Comparative Examples 1 and 2.
[0080] Fig.11 The temperature sensitivity comparison curves of the carbon-based temperature-sensitive functional inks prepared in Examples 1 and 2 and Comparative Example 3 of the present invention are shown.
[0081] Fig.12 The SEM images, photos and weight display diagrams of the grid-shaped thermosensitive unit precursor in Example 1 of the present invention are shown. Among them, (a) is the SEM image of the grid-shaped thermosensitive unit precursor; (b) to (d) are cross-sectional SEM images of the grid-shaped thermosensitive unit precursor; (e) is a photo of a unit sample showing different filament spacings; (f) is a weight display diagram of the grid-shaped thermosensitive unit precursor.
[0082] Fig.13 It is a comparison diagram of the temperature-resistance curves of the grid-shaped thermosensitive unit precursors in Examples 1 and 3 of the present invention and Comparative Examples 4 and 5. DETAILED DESCRIPTION
[0083] In order to further understand the present invention, the preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the invention. Those skilled in the art can refer to the content of this article and appropriately improve the process parameters to achieve it. It is particularly important to point out that all similar substitutions and modifications are obvious to those skilled in the art, and they are all considered to be included in the present invention. The methods and applications of the present invention have been described through preferred embodiments, and relevant personnel can obviously change or appropriately change and combine the methods and applications described herein without departing from the content, spirit and scope of the present invention to implement and apply the technology of the present invention. Although it is believed that those of ordinary skill in the art fully understand the following terms, the following definitions are still stated to help illustrate the subject matter disclosed by the present invention.
[0084] In one aspect, the present invention provides a method for preparing an ultra-thin lithium-ion battery implantable temperature sensor, which mainly comprises the following steps:
[0085] (I) Preparation of flexible substrate metal electrodes based on LISM technology
[0086] (1-1) mixing a laser sensitizer with a solvent to obtain a laser sensitizer suspension or solution, then coating the suspension or solution on the surface of a flexible polymer film, and then removing the solvent to obtain a flexible polymer film having a sensitizer coating;
[0087] The flexible polymer film material is a polyimide film (PI) or a polyethylene terephthalate film (PET);
[0088] The laser sensitizer is an organic copper sensitizer or an inorganic copper sensitizer;
[0089] (1-2) irradiating the surface of the flexible polymer film having the sensitizer coating obtained in step (1-1) with a laser, forming an activation pattern of an electrode in the irradiated area, and then washing away excess laser sensitizer to obtain a laser-activated flexible polymer film;
[0090] (1-3) immersing the laser-activated flexible polymer film obtained in step (1-2) into a metal plating solution for chemical plating to form a flexible metal electrode pattern at the activated pattern, thereby preparing a flexible substrate metal electrode based on LISM technology;
[0091] (II) Preparation of implantable temperature sensor
[0092] (2-1) The following raw materials are mixed in parts by weight to prepare a carbon-based temperature-sensitive functional ink:
[0093] Nanocellulose (CNF) 3-5 parts,
[0094] Single-walled carbon nanotubes (SWCNT) 1-1.5 parts,
[0095] 93.5 to 96 parts of solvent,
[0096] Among them, nanocellulose, single-walled carbon nanotubes and solvents totaled 100 parts;
[0097] (2-2) loading the carbon-based temperature-sensitive functional ink obtained in step (2-1) into the printing syringe of an ink direct writing 3D printer, and printing 2 to 4 layers of a grid-like thermosensitive unit precursor on the flexible substrate metal electrode obtained in step (1-3);
[0098] The printed product is then freeze-cured and dried to obtain an implantable temperature sensor.
[0099] Herein, the laser sensitizer in step (1-1) is an organic copper sensitizer or an inorganic copper sensitizer, both of which are conventional laser sensitizers in the art. Those skilled in the art can select a suitable organic copper sensitizer or inorganic copper sensitizer according to specific needs and process requirements.
[0100] In order to better illustrate the present invention and provide a preferred embodiment for reference, the laser sensitizer in step (1-1) is selected from any one of Cu2(OH)PO4, CuBr, Cu2O, copper (II)-phenanthroline complexes, and copper (II)-phthalocyaninetetrasulfonate.
[0101] In this article, the solvents described in steps (1-1) and (2-1) are conventional solvents in the field of chemical materials. Those skilled in the art can select suitable solvents according to specific needs and process requirements, and can also optimize them according to their applicable purposes. For example, in step (1-1), the solvent plays a role in uniformly dispersing the laser sensitizer so that it is suitable for scraping on the surface of the flexible polymer film material, and in step (2-1), the solvent is the main ink component in the ink direct writing 3D printing technology. Those skilled in the art can optimize them according to the conventional ink solvents for the ink direct writing 3D printing technology in the prior art.
[0102] In order to better illustrate the present invention and provide a preferred embodiment for reference, the solvent selected in steps (1-1) and (2-1) includes any one of ethanol, deionized water, ethylene glycol, ammonia water, dimethylformamide, and dimethyl sulfoxide. Theoretically, the solvents in steps (1-1) and (2-1) can be the same solvent or different solvents; in one preferred embodiment, the solvent in step (1-1) is ethanol; the solvent in step (2-1) is deionized water.
[0103] In this article, in step (1-1), the laser sensitizer and the solvent are mixed to obtain a laser sensitizer suspension or solution. The ratio of the laser sensitizer to the solvent can be directly referred to the conventional application method of the laser sensitizer in the prior art, such as the ratio recommended in the product manual. In order to better illustrate the present invention and provide an embodiment for reference, the laser sensitizer and the solvent in step (1-1) are mixed and configured at a ratio of 1g: (15-40)ml.
[0104] In one embodiment, in order to enable the irradiated area in step (1-2) to form a better activation pattern, the suspension or solution described in step (1-1) is scraped onto the surface of the flexible polymer film, preferably to form a coating of 40 to 60 μm thick, and then the solvent is removed to obtain a flexible polymer film with a sensitizer coating.
[0105] Herein, the removal of solvent in step (1-1) is performed by a conventional method for removing solvent from coatings after coating in the chemical industry. For example, when the solvent is ethanol, the ethanol is allowed to evaporate by standing at room temperature.
[0106] One of the inventive points of the present invention is that, based on the prior laser activated selective metallization (LISM) technology of the applicant of the present invention, it is found that the specific process parameters of laser irradiation will significantly affect the quality and peeling strength of the activated pattern and the flexible metal electrode pattern. The inventors of the present invention have found through a large number of orthogonal experiments that under specific laser parameters and laser irradiation times, a metal coating with uniform thickness and high peeling strength can be formed, while showing excellent continuity and fineness.
[0107] Based on the above invention, in one embodiment, the step (1-2) uses a laser to irradiate the surface of the flexible polymer film material with a sensitizer coating obtained in the step (1-1), and forms an activation pattern of an electrode in the irradiated area. Specifically, the surface of the flexible polymer film material with a sensitizer coating is irradiated with laser twice. The laser frequency of the first laser irradiation is 50kHz, the laser power is 6W, and the laser scanning speed is 2000mm / s. The laser frequency of the second laser irradiation is 50~70kHz, the laser power is 6~7W, and the laser scanning speed is 2000mm / s.
[0108] In this article, the activation pattern of the electrode is formed in the irradiated area in step (1-2), wherein the activation pattern of the electrode is selected from a conventional electrode line pattern, such as an activation pattern of an interdigitated electrode in one embodiment. Further, multiple electrode line array patterns, such as an activation pattern of an interdigitated electrode array, can also be formed based on the prior art.
[0109] It should be noted that the size and dimensions of the activated pattern of the formed electrode can be designed according to the relevant public specifications of microelectrodes in the prior art, and its size and dimensions are preferably matched with the grid-shaped thermosensitive unit precursor described below.
[0110] Herein, the excess laser sensitizer is washed away in step (1-2), usually by using the solvent in step (1-1), or other conventional methods in the art.
[0111] In this article, the metal plating solution described in step (1-3) is a metal plating solution conventionally used in the field of chemically plating metal electrodes in the present technical field. Those skilled in the art can directly select an appropriate public metal plating solution formula to configure the corresponding metal plating solution according to the existing process or actual needs. In one embodiment, the metal plating solution selected in step (1-3) includes a copper metal plating solution, a nickel metal plating solution, a silver metal plating solution, a chromium metal plating solution or a gold metal plating solution.
[0112] In one embodiment, the metal plating solution in step (1-3) is a copper metal plating solution, and chemical copper plating is performed according to the following reaction formula:
[0113] Cu 2+ +2HCHO+4OH - →Cu+2HCOO - +H2O+H2↑.
[0114] In order to better illustrate the present invention and provide an implementation method for reference, the composition of the metal plating solution in step (1-3) is: 8g / L CuSO4, 30g / L NaKC4H4O6, 3g / L EDTA, 3g / L C6H5Na3O7, 12ml / L HCHO and 150ml / L CH3OH, and the solvent is deionized water.
[0115] Herein, the chemical plating described in step (1-3) is a conventional chemical plating method in the field of chemical plating of metal electrodes. Those skilled in the art can determine the specific chemical plating process conditions according to the chemical reaction conditions of the selected metal plating solution.
[0116] In order to better illustrate the present invention and provide an implementation method for reference, when the metal plating solution is the copper metal plating solution, the chemical plating in step (1-3) is to immerse the flexible polymer film after laser activation in the metal plating solution, and stir it for 12 to 20 minutes at a temperature of 50 to 60°C to prepare a flexible substrate metal electrode based on LISM technology.
[0117] It should be noted that the preparation of the flexible substrate metal electrode based on LISM technology in step (1-3) usually also includes conventional operations such as cleaning after chemical plating. These conventional operations are common knowledge of those skilled in the art and will not be described again.
[0118] In this article, the preparation of the carbon-based temperature-sensitive functional ink follows the common knowledge in the art, and each raw material component is mixed evenly.
[0119] In order to better illustrate the present invention and provide an implementation method for reference, the method for preparing the carbon-based temperature-sensitive functional ink is to mix and stir the raw material components for 20 to 120 minutes at 20 to 35°C and 8000 to 30000 r / min.
[0120] In one embodiment, in order to better adapt the carbon-based temperature-sensitive functional ink in step (2-1), the parameters of the ink direct writing 3D printer in step (2-2) are set to the air pressure at 15-30 psi and the printing needle moving speed at 5-12 mm s -1 .
[0121] In one embodiment, the printed product is freeze-solidified and dried in step (2-2), wherein the printed product is frozen with liquid nitrogen for 2 to 10 minutes and then freeze-dried for at least 12 hours.
[0122] In this article, the 2 to 4 layers of grid-like thermal-sensitive unit precursor described in step (2-2), wherein the number of layers 2 to 4 is the number of slice layers in ink direct writing 3D printing, for example, each layer is a parallel printing wire strip formed by straight line filling printing, and the printing wire strips of adjacent layers are perpendicular to each other to form a grid structure, and therefore, there are at least 2 layers.
[0123] In one embodiment, in order to make the prepared implantable temperature sensor have ultra-light and thin characteristics in terms of size specifications, the single length of the grid-shaped thermistor unit precursor is 7-10 mm, the width is 7-10 mm, the thickness is 1.5-2 mm, and the weight is about 10-20 mg.
[0124] In one of the more preferred embodiments, in order to improve the temperature sensitivity of the prepared implantable temperature sensor, the 2 to 4 layers of grid-like thermosensitive unit precursors in step (2-2) are each composed of parallel printed wire strips formed by linear filling printing, the printing needle diameter is 0.5 to 0.7 mm, and the spacing between the printed wire strips is 0.4 to 0.6 mm.
[0125] It should be noted that when the flexible substrate metal electrode based on LISM technology obtained in step (1-3) is an electrode array, the grid-shaped thermosensitive unit precursor in step (2-2) should also form an array corresponding to the electrode array, that is, an array is formed by multiple grid-shaped thermosensitive unit precursors to finally obtain an implantable temperature sensor array.
[0126] One of the main inventive points of the present invention is that a SWCNT / CNF system ink applied to ink direct writing 3D printing technology is developed, and a thermosensitive unit precursor with a grid structure is printed and manufactured on a flexible substrate metal electrode based on LISM technology, realizing an implantable temperature sensor with high sensitivity and temperature sensitivity in a wide temperature range. LISM technology combined with ink direct writing 3D printing technology realizes the ultra-light and thin requirements of the sensor, and it is implanted in the lithium-ion soft-pack battery for single-point and multi-point temperature monitoring, which is of great significance to the thermal management and thermal design of lithium-ion batteries.
[0127] Specifically, firstly, the thermosensitive unit precursor prepared by the technology of the present invention realizes the regulation of thermistor sensitivity and temperature measurement range, and obtains a sensitivity of -1.7%K -1 , high performance characterization in the temperature sensing range of 30 to 70°C.
[0128] Secondly, the implantable temperature sensor array was implanted into the lithium-ion soft-pack battery for multi-point monitoring. The cycle performance and rate performance loss of the soft-pack battery were small. After 20 cycles of 1C rate charge and discharge, the specific capacity remained above 120mAh / g, and after 50 cycles, the specific capacity remained above 118mAh / g, and the coulomb efficiency remained above 99%. The soft-pack battery with the sensor array implanted was subjected to five charge and discharge cycles of 0.2C, 0.5C, 1C, 2C and 0.5C, with specific capacities of 130.1mAh / g, 127.3mAh / g, 113.7mAh / g, 98.1mAh / g and 128.2mAh / g. Although the specific capacity of the soft-pack battery decayed more at 2C rate, the specific capacity recovered to 128.2mAh / g after returning to 0.5C rate, showing good reversibility.
[0129] Based on the above invention points, the ultra-light and thin lithium-ion battery implantable temperature sensor provided by the present invention can be applied to lithium-ion batteries, and can realize thermal management and safety warning of lithium-ion batteries.
[0130] In order to better illustrate the present invention, on the other hand, the present invention also provides a lithium-ion soft-pack battery using the implantable temperature sensor, wherein the implantable temperature sensor is implanted between the negative electrode and the outermost diaphragm of the lithium-ion soft-pack battery, and the implantable temperature sensor is connected to a signal processing module to monitor the internal temperature of the lithium-ion soft-pack battery.
[0131] In this article, the signal processing module includes a single-chip microcomputer and its supporting control system. The resistance signal transmitted by the electrode point is converted into a digital signal through the analog-to-digital converter on the single-chip microcomputer, and transmitted to the central processing unit on the single-chip microcomputer. The temperature size and change are judged by the resistance size and change.
[0132] When the implantable temperature sensor is an implantable temperature sensor array, or when a plurality of implantable temperature sensors are implanted at different positions inside the lithium-ion soft-pack battery, multi-point temperature monitoring can be performed inside the lithium-ion soft-pack battery.
[0133] The present invention will be further explained in detail with reference to the following examples. However, it should be understood by those skilled in the art that these examples are provided for illustrative purposes only and are not intended to limit the present invention.
[0134] Example
[0135] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. The specific conditions not specified in the examples are carried out according to the conditions recommended by normal conditions or manufacturers. The reagents used or the instruments not specified by the manufacturer are all conventional products that can be obtained commercially. The application should not be construed as being limited to the specific examples described.
[0136] 1. Raw materials
[0137]
[0138]
[0139] 2. Preparation method
[0140] (I) Preparation of flexible substrate metal electrodes based on LISM technology
[0141] (1-1) 1 g of laser sensitizer Cu2(OH)PO4 was mixed with 20 mL of ethanol to obtain a laser sensitizer suspension, and then the suspension was scraped onto the surface of a 100 μm thick polyimide film (PI) to form a 40 μm thick coating, and then the ethanol was evaporated to obtain a PI / Cu2(OH)PO4 film;
[0142] (1-2) irradiating the surface of the PI / Cu2(OH)PO4 film obtained in step (1-1) with a laser, and forming an activation pattern of interdigitated electrodes in the irradiated area, and then washing away excess laser sensitizer to obtain a laser-activated flexible polymer film;
[0143] Specifically, the surface of the PI / Cu2(OH)PO4 film was subjected to laser irradiation twice, the laser frequency of the first laser irradiation was 50kHz, the laser power was 6W, the laser scanning speed was 2000mm / s, and the laser frequency of the second laser irradiation was 60kHz, the laser power was 7W, and the laser scanning speed was 2000mm / s;
[0144] (1-3) immersing the laser-activated flexible polymer film obtained in step (1-2) into a copper metal plating solution for chemical plating to form a flexible metal interdigital electrode pattern at the activated pattern, thereby preparing a flexible substrate metal interdigital electrode based on LISM technology;
[0145] The copper metal plating solution is composed of 8 g / L CuSO4, 30 g / L NaKC4H4O6, 3 g / L EDTA, 3 g / L C6H5Na3O7, 12 ml / L HCHO and 150 ml / L CH3OH, and the solvent is deionized water; the chemical plating temperature is 52°C, the time is 12 minutes, and stirring is continued during the process; after the chemical plating is completed, the solution is cleaned once with deionized water and ethanol, and finally dried;
[0146] (II) Preparation of implantable temperature sensor
[0147] (2-1) The following raw materials are mixed in parts by weight to prepare a carbon-based temperature-sensitive functional ink:
[0148] Nanocellulose (CNF) 3-5 parts,
[0149] Single-walled carbon nanotubes (SWCNT) 1-1.5 parts,
[0150] 93.5-96 parts of deionized water,
[0151] Among them, nanocellulose, single-walled carbon nanotubes, and deionized water totaled 100 parts;
[0152] (2-2) The carbon-based temperature-sensitive functional ink obtained in step (2-1) is loaded into the printing syringe of the ink direct writing 3D printer, and two layers of grid-shaped thermal-sensitive unit precursor are printed on the metal interdigitated electrode of the flexible substrate obtained in step (1-3); the parameters of the ink direct writing 3D printer are set as follows: the air pressure is set at 20 psi, the printing needle movement speed is set at 6 mm s -1 , the printing needle diameter is 0.5mm;
[0153] The single length of the grid-shaped thermal-sensitive unit precursor is 7 mm, the width is 7 mm, the thickness is 1.5 mm, the spacing between the printed wire strips is 0.4-0.6 mm, and the weight is about 10 mg; the grid-shaped thermal-sensitive unit precursor covers the interdigital part of the metal interdigital electrode of the flexible substrate;
[0154] The printed product was then frozen with liquid nitrogen for 2 minutes, and the frozen sample was placed in a freeze dryer for freeze drying for 12 hours to obtain an implantable temperature sensor.
[0155] Example 1
[0156] Example 1 is according to the above-mentioned "2. Preparation method" steps, wherein in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1.5 parts; in step (2-2), the spacing between the printed wire strips is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a sample.
[0157] Example 2
[0158] Example 2 is according to the above-mentioned "2. Preparation method" steps, wherein in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1 part; in step (2-2), the spacing between the printed filaments is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a sample.
[0159] Example 3
[0160] Example 3 is according to the above-mentioned "2. Preparation method" steps, wherein in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1.5 parts; in step (2-2), the spacing between the printed filaments is 0.4 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a sample.
[0161] Example 4
[0162] Example 4 is according to the above-mentioned "2. Preparation method" steps, wherein in step (2-1), the nanocellulose is 3.3 parts and the single-walled carbon nanotube is 1 part; in step (2-2), the spacing between the printed filaments is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a sample.
[0163] Comparative Example 1
[0164] Comparative Example 1 follows the steps of “2. Preparation method” above, except that in step (2-1), the nanocellulose is 2.5 parts, the single-walled carbon nanotube is 1 part, and the deionized water is 96.5 parts; in step (2-2), the spacing between the printed filaments is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a comparative sample.
[0165] Comparative Example 2
[0166] Comparative Example 2 follows the steps of “2. Preparation method” above, except that in step (2-1), the nanocellulose is 10 parts, the single-walled carbon nanotube is 1 part, and the deionized water is 89 parts; in step (2-2), the spacing between the printed filaments is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a comparative sample.
[0167] Comparative Example 3
[0168] Comparative Example 3 follows the steps of “2. Preparation method” above, except that in step (2-1), the nanocellulose is 5 parts, the single-walled carbon nanotube is 2 parts, and the deionized water is 93 parts; in step (2-2), the spacing between the printed filaments is 0.6 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a comparative sample.
[0169] Comparative Example 4
[0170] Comparative Example 4 follows the steps of “2. Preparation method” above, except that in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1.5 parts; in step (2-2), the spacing between the printed filaments is 0 mm (i.e., fully filled printing); and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a comparative sample.
[0171] Comparative Example 5
[0172] Comparative Example 5 follows the steps of “2. Preparation method” above, except that in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1.5 parts; in step (2-2), the spacing between the printed wire strips is 0.2 mm; and finally, an implantable temperature sensor having an interdigitated electrode and a corresponding single grid-shaped thermistor unit precursor is prepared as a comparative sample.
[0173] Example 5
[0174] Example 5 is in accordance with the steps of "2. Preparation method" above, wherein in step (2-1), the nanocellulose is 5 parts and the single-walled carbon nanotube is 1.5 parts; in step (2-2), the spacing between the printed wire strips is 0.6 mm; and finally, an implantable temperature sensor array having five interdigitated electrodes and corresponding five grid-shaped thermosensitive unit precursors is prepared as a sample, such as Figure 8 As shown, its thickness is measured to be 0.17 mm and its weight is approximately 430 mg.
[0175] 3. Test methods
[0176] Scanning electron microscopy: A scanning electron microscope (SEM) was used to observe the morphological evolution of the PI film surface during laser-induced selective metallization and to evaluate the quality and fineness of the copper layer.
[0177] Energy Dispersive Spectroscopy Elemental Analysis: Energy Dispersive Spectroscopy (EDS) is used to characterize the element distribution during the metallization process.
[0178] Optical microscope: An optical microscope (OM) is used to observe the shape and details of metal circuits and metal patterns.
[0179] Raman spectroscopy: Raman spectroscopy uses a 532nm excited diode laser and a 25μm confocal pinhole to record the Raman spectrum of the PI film surface after laser activation.
[0180] X-ray photoelectron spectrometer: X-ray photoelectron spectrometer (XPS) is used to study the generation process of active species on the surface of PI films and the valence state of elements during the metallization process.
[0181] Four-probe conductivity tester: Four-probe conductivity tester is used to test the conductivity of various metal circuits and metallization pattern copper layers manufactured by metallization.
[0182] Ultraviolet-visible-near-infrared spectroscopy: Ultraviolet-visible-near-infrared spectroscopy (UV-Vis-IR) is used to characterize the absorption degree of laser sensitizers to light of various wavelengths.
[0183] Copper layer adhesion tester: The adhesion strength between the copper-plated layer and the polymer substrate is measured by the ASTM D3359B method. Use a grid knife to draw a small square grid of 1mm×1mm in the copper-plated layer area. Then, stick the Scotch3M 600-1PK test tape to the grid area and quickly tear off the tape. The grade of adhesion strength is judged according to the area where the copper layer falls off. In the ASTM D3359 grading standard, the higher the grade, the higher the adhesion between the polymer substrate and the copper-plated layer. 0B (peeling area>65%); 1B (peeling area of 35%-65%); 2B (peeling area of the grid is 15%-35%); 3B (peeling area of the grid is 5%-15%); 4B (peeling area of the grid is 5%); 5B (no peeling of any grid).
[0184] Rotational rheology instrument: By measuring rheological data such as shear rate, shear stress, stress-strain amplitude, etc., the viscosity, storage modulus, loss modulus and other parameters of the sample are calculated. This paper uses the AR2000 rotational rheometer of IA Company in the United States. The parallel plate mode is used to characterize the rheological properties of the ink. The ink is placed between flat plates with a gap of 1mm, and the viscosity of the ink is tested at room temperature with shear rate changes; the oscillation mode is used to test the storage modulus and loss modulus of the ink at room temperature.
[0185] Scanning electron microscope: Scanning electron microscope uses high-energy electron beam to interact with samples to stimulate various physical information, collect and amplify this information in imaging to achieve the purpose of characterizing the microscopic morphology of the material. This article uses the Quanta scanning electron microscope produced by FEI Company in the United States. The sample is attached to the sample stage with conductive tape. After gold spraying, the surface and cross-sectional morphology of the sample are observed under vacuum conditions.
[0186] Optical Microscopy: Use an optical microscope to observe the details of the printed grid as well as the details of the sensor / sensor array.
[0187] Infrared Camera: Use an infrared camera to evaluate the heat transfer performance of thermal cells.
[0188] Blue Electric Test System: Use the Blue Electric Test System to perform charge and discharge tests on soft-pack batteries at different rates, with a lower voltage limit of 2V and an upper voltage limit of 4V. Record relevant data such as voltage-time, voltage-specific capacity, and coulombic efficiency.
[0189] Thermal sensing performance test:
[0190] (1) Sensor calibration: Place the sensor inside the oven, precisely control the temperature, and monitor the sensor resistance change in real time to obtain the temperature-resistance curve, which is used as the sensor calibration curve;
[0191] (2) Temperature monitoring: attach the sensor to the surface of the object to be measured, and use the temperature monitoring program to monitor the surface temperature of the object to be measured in real time;
[0192] (3) Heat source position monitoring: The sensor is attached to the glass plate, the heating rod is placed at different positions of the sensor, and the heat source monitoring program is used to monitor the real-time heat source position, and the monitoring results are displayed on the LED screen. The heat source is moved through different positions in sequence to evaluate the sensing system's monitoring of the heat source path.
[0193] Finite element simulation calculation: This paper uses the multi-physics field direct coupling analysis software COMSOL, relying on appropriate three-dimensional mesh division to obtain higher accuracy requirements, and introduces the finite element method into the internal temperature monitoring of the battery. Using the multi-physics field of solid heat transfer and convection heat transfer, add steady-state or transient research, set the thermodynamic properties of each battery material, give initial conditions and boundary conditions, and finally calculate and obtain simulation results by optimizing the subdivided mesh.
[0194] 4. Test results
[0195] The manufacturing process of the implantable sensor / implantable temperature sensor array provided by the present invention is as follows: Figure 1 shown.
[0196] like Figure 2As shown, the temperature sensor and the implantable temperature sensor array are respectively implanted into the lithium-ion soft-pack battery, and the soft-pack battery is assembled in the order of diaphragm-positive electrode tab-positive electrode-diaphragm-negative electrode-negative electrode tab-diaphragm, and the sensor / sensor array is implanted between the negative electrode and the outermost diaphragm, and the battery cell equipped with the sensor / sensor array is loaded into the aluminum-plastic film, and 1M LiPF6 in EC:DMC=1:1Vol% electrolyte is injected in the glove box, and it is packaged into a soft-pack battery using a vacuum heat sealer. The capacity of the soft-pack battery is calculated in order to set the subsequent battery test conditions. The active material content of the lithium iron phosphate positive electrode sheet is 90%, and the area content is 13mg / cm 2 , theoretical capacity 135mAh / g.
[0197] like Figure 3 As shown in the figure, a laser irradiation parameter matrix was designed to correspond to different laser powers and laser frequencies, and the effects of laser frequency and laser power on laser-activated selective metallization were studied. Figure 3 As shown in (a), the parameter matrix contains 90 squares, corresponding to laser frequencies of 10kHz to 100kHz and laser powers of 1W (10%) to 10W (100%). Laser activation is performed according to the parameters corresponding to each small square, and the results are shown in Figure 3 (b) When the laser power is less than 3W, the copper layer cannot be plated regardless of whether the laser frequency is changed. This is because the laser energy is too low to reach the minimum energy required to activate Cu2(OH)PO4. Similarly, when the laser frequency is too low, it is also very difficult to activate Cu2(OH)PO4. Figure 2 The results show that when the frequency is less than 20kHz, a larger laser power is required to effectively activate Cu2(OH)PO4. However, excessive power and frequency are accompanied by severe thermal effects when fully activating Cu2(OH)PO4, which can cause damage to the surface structure of the PI film and carbonization. When the PI film is carbonized, the plating effect deteriorates.
[0198] The results show that when the laser frequency is 50kHz and the laser power is 6W, the quality of the electroless copper layer is significantly better than that of other areas. Therefore, this parameter is selected as the optimal laser parameter for the first laser irradiation.
[0199] Although the pure PI film does not absorb near-infrared lasers significantly, micro-carbonization appears on its surface after the first laser irradiation. These carbonization points will enhance the PI film's absorption of near-infrared light. Therefore, the laser-activated PI film was subjected to a second laser irradiation and chemical plating. The results are as follows: Figure 4As shown in the figure. After the second laser irradiation, the minimum laser power for chemical plating of the PI film is 3W. The overall laser processing window is significantly widened compared with the first laser processing, and the copper layer can also be plated in the high power and high frequency area. It is worth noting that the laser sensitizer has a strong selectivity for laser parameters in addition to the minimum activation energy. Figure 4 As shown in the figure, after the second laser irradiation, the morphology of the PI film has changed significantly in the area of laser frequency of 60kHz and power of 6W to 10W. According to the results after chemical copper plating, the second laser irradiation has the best effect in the area of laser frequency of 50 to 70kHz and power of 6W to 7W.
[0200] In order to explore the changes of PI film morphology caused by laser-induced selective metallization, the morphology of PI before and after laser activation was characterized. Figure 5 (a) and (b) are SEM photos of the surface of the PI film sample after the first laser irradiation. It can be seen that there is a clear boundary between the laser-activated and non-activated areas. The surface of the non-laser-activated area is smooth, while bubbles and holes are formed on the surface of the sample in the laser-activated area. The chemical copper plating reaction occurs preferentially in the rough area. The reason for the generation of bubbles and holes is the heat released after the action of the laser and Cu2(OH)PO4. These rough microstructures greatly improve the adhesion of the chemically plated metal circuit on the surface of the PI film. The PI film after the second laser irradiation. Its surface has a rougher microstructure, and the boundary between the processed area and the unprocessed area is more obvious. The size of these rough structures is about tens of μm, which is slightly larger than the preset spot size of the laser. Due to the thermal effect of the near-infrared laser, the spot size is smaller than the size of the minimum processing point. And the adjacent processing points will also affect each other, resulting in uneven size and shape of the rough microstructure formed. In addition, it is worth noting that rough surfaces are easier to plate metal than smooth surfaces. This is because the copper layer only grows on the surface of the smooth surface during chemical plating, and the interface between the copper layer and the polymer is very flat, without abundant riveting points. When chemical plating is performed on a rough surface, due to the presence of holes and depressions on the rough surface, the chemical plating solution will invade and plate inside. As the chemical plating progresses, when copper fills these rough structures, it diffuses and grows, connects with each other, and finally forms a complete copper layer. Since part of the copper layer is embedded in the rough microstructure, the adhesion of the copper layer is greatly improved, and a thicker copper layer can be plated without falling off. Compared with a smooth surface, when the copper layer exceeds 10μm, its adhesion will be greatly reduced. These rough microstructures are the key to plating a thicker copper layer.
[0201] The pattern of the interdigital electrode was designed by computer, and the laser was used for the first and second laser irradiation respectively. The surface of the processed PI film was observed. The results are as follows: Figure 6 As shown. Figure 6 As shown in (a), after the first laser irradiation, the PI film produces a rough morphology and carbonization within the preset shape, but the carbonization is not uniform. The carbonization degree of the contour of the interdigitated electrode is higher, while the carbonization degree of the internal shape of the contour is lower. This is related to the routing method during laser processing. The laser adopts a line scanning processing method for processing. At the end of each scanning line and the beginning of the next scanning line, the processing time interval is short, resulting in a greater accumulation of thermal effects at the contour position, and ultimately a greater degree of carbonization is produced at the contour. Figure 6 (b) is the surface of the PI film after the second laser irradiation. The overall carbonization degree is higher than that of the first laser irradiation. Similarly, the carbonization degree at the contour is also higher than that inside the contour, but the carbonization degree inside the contour is more uniform than that after the first laser irradiation, which can make the subsequent chemically plated copper layer more uniform and dense.
[0202] The carbonization produced by laser processing was characterized in detail. The interaction between near-infrared laser and PI film will produce carbonization. The Raman spectrum results show that the carbonization produced by the second laser irradiation is more uniform, while the carbonization on the surface of the PI film irradiated by the first laser is not uniform. This is because the micro-carbonized area produced by the first laser irradiation can absorb more heat during the second laser irradiation, producing more sufficient and uniform carbonization. The Raman spectra corresponding to the red, yellow, green and blue areas in the Raman imaging are compared, and it can be clearly seen that the intensity of amorphous carbon produced by the second laser irradiation increases.
[0203] The PI film after secondary laser irradiation according to the shape of the interdigital electrode was selected for chemical copper plating, and the copper layer plated on it was observed. The results are as follows: Figure 7 As shown in (a) and (b), chemical copper plating occurs in the laser-processed area, and the copper layer formed is very dense and highly continuous.
[0204] Figure 7 (c) and (d) are SEM images of the PI film surface after chemical copper plating. The copper layer surface is smooth. Further observation of the details of the metal circuit shows that the interdigital line width of the interdigital electrode is 536.4μm, the interdigital spacing is 140.6μm, and the actual line width is larger than the preset line width of 500μm. This is due to the thermal effect during the laser activation process. This thermal effect is inevitable. After calculation, the actual line width exceeds the preset line width by 7.2%.
[0205] In summary, the changes in the morphology of the PI film caused by laser activated selective metallization and laser induced carbonization enhance its surface roughness, provide more deposition sites for chemical copper plating, and thus improve the adhesion and selectivity of the metal circuits on the PI film.
[0206] In order to obtain the sample with the best comprehensive performance, we systematically studied the effect of ink formulation on rheological properties, sensitivity, temperature range and microstructure. While keeping the SWCNT content unchanged (1wt.%), the effect of CNF content (2.5, 3.3, 5, 10wt.%) on the rheological properties of the composite ink was studied. Fig. 9 As shown in (a), the apparent viscosity of the ink exhibits typical shear thinning properties, which causes the ink to transform from a high viscosity state to a fluid state, thus making pneumatic continuous printing possible. The storage modulus G' and loss modulus G" are respectively Fig. 9 (b) and (c). The higher storage modulus indicates that the viscoelastic ink has solid material properties, which can ensure stable shape retention and thus maintain the intended printed structure, while the solid-liquid transition causes the ink to flow and deposit after a critical shear stress.
[0207] In addition, we also conducted a comprehensive comparison of the processability, sensitivity, and temperature monitoring range of printed thermistors with different CNF contents, e.g. Fig.10 Finally, the ink with 5wt% CNF content was selected as the best ink.
[0208] Another important factor affecting the sensing performance of the sample is the content of conductive filler. Fig.11 The sensing performance of samples with different SWCNT contents (1, 1.5, 2 wt.%) is shown. As the SWCNT content increases, the sensitivity of the sample increases (-1.3% K -1 、-1.7%K -1 、-2.1%K -1 ), but the initial resistance of the sample is reduced (39.7kΩ, 18.3kΩ, 9.1kΩ). Although the sensitivity is high and the temperature changes can be monitored more sensitively, the initial resistance is small. During the heating process, the sample with a small resistance will quickly enter the conductive state from the semi-conductive state. At this time, the SWCNT conductive network in the sample has been constructed very well. It is difficult to significantly reduce the resistance value by heating again, so the thermistor can no longer effectively sense temperature changes. Therefore, we selected an ink with a SWCNT content of 1.5wt.% as the best ink, and the printed sample has excellent sensitivity (-1.7%K -1 ) and a suitable initial resistance (18.3kΩ).
[0209] The grid-shaped thermal-sensitive unit precursor is designed with a grid structure, which is composed of two layers of printed silk strips that are perpendicular to each other, ensuring the temperature sensing in the horizontal and vertical directions. Fig.12 (a) to (d) are SEM images of the surface and cross-section of the grid-shaped thermosensitive unit precursor. It can be seen that a porous structure is formed inside, which is the key to sensing temperature. Fig.12(e) shows the grid-like thermosensitive unit precursor with different filament spacing, and the printed thermosensitive unit has a very small mass due to its porous structure, e.g. Fig.12 (f) as shown.
[0210] Due to the advantages of 3D printing in shape and structure design, samples with different wire spacing were designed and their temperature-resistance behavior was tested. The results are as follows: Fig.13 shown.
[0211] The results show that when the spacing between the printed wire strips is small, the temperature-resistance curve fluctuates greatly, and the temperature and resistance cannot correspond one-to-one. Only when the spacing between the wire strips increases to 0.6 mm, the temperature-resistance curve of the two-layer grid-shaped thermistor unit precursor becomes smoother, and the resistance and temperature can correspond one-to-one to achieve temperature monitoring.
[0212] For the implantable temperature sensor array prepared in Example 5, considering its large size, implanting it into the soft-pack battery may affect the battery performance. Therefore, the performance of the soft-pack battery implanted with the sensor array was evaluated. First, the battery was charged and discharged 20 times at a rate of 1C. The theoretical specific capacity of the soft-pack battery is 135mAh / g, and the specific capacity of the first cycle test of the soft pack is 126.9mAh / g, which is close to the theoretical specific capacity. The specific capacity of the soft-pack battery implanted with the sensor array after 5, 10, 15 and 20 cycles was 126.1, 124.9, 123.4, and 120.3mAh / g, respectively, and the specific capacity decay was small.
[0213] In addition, the coulombic efficiency of the soft-pack battery implanted with the sensor array during 50 charge and discharge cycles at 1C rate was calculated. During the 50 charge and discharge cycles, the charge capacity and discharge capacity were maintained above 118mAh / g, and the coulombic efficiency was maintained above 99%, which was due to some irreversible side reactions inside the battery. From the above results, it can be seen that the cycle performance loss of the soft-pack battery implanted with the sensor array is very small, and the 1C charge and discharge test can still be carried out normally.
[0214] Since the battery will also be charged and discharged at low rates (trickle charge and discharge, etc.) and high rates (fast charge and discharge, pulse charge and discharge, etc.) during service. The soft-pack battery implanted with the sensor array was tested for charge and discharge at 0.2C, 0.5C, 1C and 2C, and the cycle test was performed 5 times at each rate. After the 2C rate test, 5 0.5C charge and discharge cycles were performed. The results show that the charge capacity of 130.1mAh / g at a rate of 0.2C is very close to its theoretical capacity. At a rate of 0.5C, its charge capacity is 127.3mAh / g, and at a rate of 1C, it is 117.7mAh / g. At a rate of 2C, the charge capacity is 98.1mAh / g, and the capacity has a large attenuation. However, when the test rate is restored to 0.5C, the charge capacity of the soft-pack battery is restored to 128.2mAh / g, indicating that the soft-pack battery has good reversibility. And the charge and discharge rates at different rates are maintained above 98.8%.
Claims
1. A method for preparing an ultra-thin lithium-ion battery implantable temperature sensor, characterized in that The main steps include: (I) Preparation of flexible substrate metal electrodes based on LISM technology (1-1) mixing a laser sensitizer with a solvent to obtain a laser sensitizer suspension or solution, then coating the suspension or solution on the surface of a flexible polymer film, and then removing the solvent to obtain a flexible polymer film having a sensitizer coating; The flexible polymer film material is a polyimide film or a polyethylene terephthalate film; The laser sensitizer is an organic copper sensitizer or an inorganic copper sensitizer; (1-2) irradiating the surface of the flexible polymer film having the sensitizer coating obtained in step (1-1) with a laser, forming an activation pattern of an electrode in the irradiated area, and then washing away excess laser sensitizer to obtain a laser-activated flexible polymer film; (1-3) immersing the laser-activated flexible polymer film obtained in step (1-2) into a metal plating solution for chemical plating to form a flexible metal electrode pattern at the activated pattern, thereby preparing a flexible substrate metal electrode based on LISM technology; (II) Preparation of implantable temperature sensor (2-1) The following raw materials are mixed in parts by weight to prepare a carbon-based temperature-sensitive functional ink: 3-5 parts of nanocellulose, 1-1.5 parts of single-walled carbon nanotubes, 93.5 to 96 parts of solvent, Among them, nanocellulose, single-walled carbon nanotubes and solvents totaled 100 parts; (2-2) loading the carbon-based temperature-sensitive functional ink obtained in step (2-1) into the printing syringe of an ink direct writing 3D printer, and printing 2 to 4 layers of a grid-like thermosensitive unit precursor on the flexible substrate metal electrode obtained in step (1-3); The printed product is then freeze-cured and dried to obtain an implantable temperature sensor.
2. The preparation method according to claim 1, characterized in that: The laser sensitizer in step (1-1) includes any one of Cu2(OH)PO4, CuBr, Cu2O, copper (II)-o-phenanthroline complex, and copper (II)-phthalocyanine sulfonate.
3. The preparation method according to claim 1, characterized in that: The solvent in steps (1-1) and (2-1) includes any one of ethanol, deionized water, ethylene glycol, aqueous ammonia, dimethylformamide, and dimethyl sulfoxide.
4. The preparation method according to claim 1, characterized in that: In step (1-1), the laser sensitizer and the solvent are mixed in a ratio of 1 g: (15-40) ml.
5. The preparation method according to claim 1, characterized in that: The step (1-2) is to irradiate the surface of the flexible polymer film material with a sensitizer coating obtained in the step (1-1) with a laser, and form an activation pattern of an electrode in the irradiated area. Specifically, the surface of the flexible polymer film material with a sensitizer coating is irradiated with laser twice. The laser frequency of the first laser irradiation is 50kHz, the laser power is 6W, and the laser scanning speed is 2000mm / s. The laser frequency of the second laser irradiation is 50-70kHz, the laser power is 6-7W, and the laser scanning speed is 2000mm / s.
6. The preparation method according to claim 1, characterized in that: The metal plating solution in step (1-3) is a copper metal plating solution, and chemical copper plating is performed according to the following reaction formula: With 2+ +2HCHO+4OH - →Cu+2HCOO - +H2O+H2↑.
7. The preparation method according to claim 1, characterized in that: The single length of the grid-shaped thermosensitive unit precursor in step (2-2) is 7 to 10 mm, the width is 7 to 10 mm, and the thickness is 1.5 to 2 mm.
8. The preparation method according to claim 1, characterized in that: In step (2-2), the 2 to 4 layers of the grid-shaped thermal-sensitive unit precursor are each formed by parallel printing strips formed by linear filling printing, the printing needle diameter is 0.5 to 0.7 mm, and the spacing between the printing strips is 0.4 to 0.6 mm.
9. An implantable temperature sensor prepared by the method for preparing an ultra-thin lithium-ion battery implantable temperature sensor as claimed in claim 1.
10. The implantable temperature sensor as claimed in claim 9 is applied to a lithium-ion battery.
Citation Information
Patent Citations
A manufacturing method of a multi-point internal temperature monitoring integrated battery
CN109065961A
Flexible liquid metal pattern based on laser activation selective metallization and preparation method thereof
CN113727531A
Flexible bendable metal pattern based on laser technology and preparation method and application thereof
CN114786342A
Simple power battery temperature sensor implantation method and temperature sensor
CN115663322A
PEO-based implantable battery temperature sensor and preparation method and application thereof
CN117091727A
Cited By
Underwater conformal high-density array pressure sensing shell and preparation method thereof
CN121498949A